Scleritis after Proton Therapy in Uveal Melanoma - Passarin, O.; Zografos, L.; Schalenbourg, A.; Moulin, A.; Guex-Crosier, Y. (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: Sclera is a very radioresistant tissue and scleritis after proton therapy has not been described so far.History and Signs: Four female patients, aged between 31 and 74 years, were treated with proton therapy for uveal melanoma (height range: 2.2 − 3.5 mm), located in the macula, the superior equator and 2 in the ciliary body. All patients had a history of a previous or active inflammatory disease and developed scleritis after radiotherapy.Therapy and Outcome: Two patients had infectious scleritis and were treated with adequate antibiotic therapy. After systemic corticotherapy, 3 patients recovered completely; the remaining patient was managed with additional immunosuppressive treatment as well as a conjunctival and scleral graft, but has not become pain free yet. Conclusion: Scleritis is a possible complication after proton therapy, probably on an ischemic basis, where there is a predisposing factor such as inflammatory systemic disease.
Keywords: syphilis; posterior scleritis; anterior scleritis; proton beam therapy; uveal melanoma